Diagnostic accuracy of ultrasound in common shoulder pathologies: a retrospective cohort study and literature review - Mohamed, Osama; Sam, Jerry; Pydah, Satya Kanth; Cheema, Kanwalnaini (International Journal of Research in Orthopaedics, 2025)
Background: This study aims to evaluate the diagnostic accuracy of shoulder ultrasound in detecting common shoulder pathologies, including rotator cuff tears, AC joint diseases, glenohumeral joint diseases, subacromial impingement, and long head of biceps conditions. The research question focuses on comparing ultrasound findings with arthroscopy results. Methods: We conducted a retrospective cohort study of 60 patients who underwent preoperative ultrasound followed by shoulder arthroscopy. Sensitivity, specificity, and diagnostic accuracy were calculated for each pathology, comparing ultrasound to arthroscopic findings. Results: Ultrasound demonstrated high sensitivity (90%) for detecting rotator cuff tears but showed lower sensitivity and specificity for AC joint diseases, subacromial impingement, and glenohumeral joint diseases. Ultrasound was particularly limited in identifying early biceps tendon pathologies. Conclusions: Ultrasound is highly sensitive for diagnosing rotator cuff tears and serves as a valuable initial diagnostic tool. However, it is less reliable for other shoulder pathologies, where additional imaging modalities may be needed to confirm diagnoses. Improved operator training could enhance diagnostic accuracy.